2017
DOI: 10.3847/1538-4357/aa8f42
|View full text |Cite
|
Sign up to set email alerts
|

Type II Supernova Spectral Diversity. II. Spectroscopic and Photometric Correlations

Abstract: We present an analysis of observed trends and correlations between a large range of spectral and photometric parameters of more than 100 type II supernovae (SNe II), during the photospheric phase. We define a common epoch for all SNe of 50 days post-explosion where the majority of the sample is likely to be under similar physical conditions. Several correlation matrices are produced to search for interesting trends between more than 30 distinct light-curve and spectral properties that characterize the diversit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
93
1
31

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 76 publications
(132 citation statements)
references
References 69 publications
7
93
1
31
Order By: Relevance
“…The correlation between absolute peak magnitudes and expansion velocity was recently confirmed by Gutiérrez et al (2017), who also confirmed the previous claim of Anderson et al (2014a) and Valenti et al (2016) that brighter SNe II show shorter plateau phases and steeper decline rates. Similar results were also reported by Galbany et al (2016) by analyzing the light curves of a large sample of SNe II.…”
Section: Comparison With Other Sne IIsupporting
confidence: 76%
“…The correlation between absolute peak magnitudes and expansion velocity was recently confirmed by Gutiérrez et al (2017), who also confirmed the previous claim of Anderson et al (2014a) and Valenti et al (2016) that brighter SNe II show shorter plateau phases and steeper decline rates. Similar results were also reported by Galbany et al (2016) by analyzing the light curves of a large sample of SNe II.…”
Section: Comparison With Other Sne IIsupporting
confidence: 76%
“…This SN II sample exhibits a range of Hα expansion velocities (1500 < vHα < 9600 km s −1 ) and pEWs of lines, presumably linked to the diversity in the explosion energies, progenitor radius and metallicity of SNe II. As noted in Gutiérrez et al (2017b) Ca II H&K H 4340 Fe II 4629 H 4861 Fe II 4924 Fe II 5018 Fe II 5169 Sc II 5527 Na I D Ba II 6142 Sc II 6245 Si II 6355 H 6563 O I 7770 Ca II 8662 Ca II weaker metal lines. The continuum of SN 2015an matches well with that of SN LSQ13fn and neither of them has a conspicuous Na i D line at this phase, as compared to the other SNe.…”
Section: Comparison Of Plateau Spectramentioning
confidence: 75%
“…SN 2015an displays some peculiar characteristics, in addition to the usual properties of SNe II, thereby necessitating the cognizance of the status of SN 2015an in the SNe II population before heading for the comparison with a sample of events. To this aim, we plotted the pseudo-equivalent widths (pEW) of the prominent lines vs Hα velocity at 50 d of SN 2015an along with a sample of 122 SNe II from Gutiérrez et al (2017b) in Fig. 10.…”
Section: Comparison Of Plateau Spectramentioning
confidence: 99%
See 2 more Smart Citations